Factors determining shopping and selection of retail store outlets, A study (International Journal of Scientific Research and Management (IJSRM), 2023)
Retail business is in the limelight nowadays. Not only are their margins getting bigger but also are the sizes of the outlets. To intrude into the retail industry a questionnaire was designed wherein the following questions were asked. First of all the factors that drive customers to shop at certain and particular stores over others in the retail industry of Goa were looked into. Secondly, if there was any correlation between store digitization and consumer buying satisfaction. Thirdly, if there was any correlation between consumer buying behavior and brand loyalty. And lastly if there was any correlation between retail discount and consumer footfall. The findings were as follows: nearness to the residence was ranked number 1, followed by quality of the product, assortment of merchandise, ambience, discounts given and knowledgeable staff in the store. A low level of correlation existed between digitalization and consumer buying satisfaction, a high level of correlation existed between consumer buying behavior and brand loyalty and a high correlation existed between retail discount and store reputation.